The Urgency of Changing Student Behavior in Classroom Learning After the Covid-19 Pandemic - Puspitasari, Riska; Wulandari, Triyana; Pitri, Alisya (CV. Zabags Qu Publish, 2023)
In this study, we wanted to know the urgency of changing student behavior in learning after the Covid-19 pandemic, which has been lived for almost 2 years studying at home or hybrid, and now almost all levels of education have opened face-to-face/offline classes again. There are indications of changes in student behavior when returning to face-to-face learning at school. The purpose of this study was to describe changes in student behavior in face-to-face learning in post-pandemic classes, both in terms of knowledge, attitudes and skills. To answer this, this study used a qualitative descriptive design with interviews conducted with teachers. The result is that there are positive and negative changes in student behavior at the Madrasah Tsanawiyah level. Changes in post-pandemic student behavior must be understood by teachers, parents, and the students themselves so that learning can be carried out better. Technology can indeed facilitate human work, but at least until now technology has not been able to completely replace the teacher's task as face-to-face educators.